ANALYSIS OF ADOLESCENT REPRODUCTIVE HEALTH KNOWLEDGE ON PREMARITAL SEXUAL ATTITUDE - Devy Putri Nursanti; Eri Puji Kumalasari; Aan Setyaningsih; Julia Siekmans; Vera Wabeke (Journal for Quality in Women's Health, 2022)
Background : The lack of knowledge about adolescent reproductive health can affect adolescent attitudes about premarital sex which creates the risk of unhealthy sexual acts that affect reproductive health. This study aims to determine the effect of adolescent reproductive health knowledge on premarital sexual attitudes. Method : This study used an observational analytic survey method with a cross sectional approach. The sample was taken using Proportional Random Sampling with a sample of 60 respondents, namely 21 students of class X, 17 students of class XI and 22 students of class XII, then analyzed using the Spearman Rank Test. Results : The P-value is 0.021 < (α = 0.05), which means that there is a relationship between adolescent reproductive health knowledge and premarital sexual attitudes. Conclution : Adolescents who have good knowledge about reproductive health will have a positive attitude in preventing teenage pregnancy which is included in premarital sexual attitudes